2000
DOI: 10.4049/jimmunol.165.6.3004
|View full text |Cite
|
Sign up to set email alerts
|

A NK1.1+ Thymocyte-Derived TCR β-Chain Transgene Promotes Positive Selection of Thymic NK1.1+ αβ T Cells

Abstract: As a consequence of the peptide specificity of intrathymic positive selection, mice transgenic for a rearranged TCR β-chain derived from conventional αβ T lymphocytes frequently carry mature T cells with significant skewing in the repertoire of the companion α-chain. To assess the generality of such an influence, we generated transgenic (Tg) mice expressing a β-chain derived from nonclassical, NK1.1+ αβ T cells, the thymus-derived, CD1.1-specific DN32H6 T cell hybridoma. Results of the sequence analysis of gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
(43 reference statements)
2
4
0
Order By: Relevance
“…We therefore used an alternative strategy based on the transgenic expression of a Vβ6 + TCRβ chain from one of the iVα19 T-T hybridoma. As shown previously for mainstream T cells [26] and NKT cells [27], the frequency of the iVα19-Jα33 TCRα chain was increased in these mice in a MR1-dependent manner (see Figure S3D and Text S1). …”
Section: Resultssupporting
confidence: 81%
“…We therefore used an alternative strategy based on the transgenic expression of a Vβ6 + TCRβ chain from one of the iVα19 T-T hybridoma. As shown previously for mainstream T cells [26] and NKT cells [27], the frequency of the iVα19-Jα33 TCRα chain was increased in these mice in a MR1-dependent manner (see Figure S3D and Text S1). …”
Section: Resultssupporting
confidence: 81%
“…Another possibility is that the thymic architecture in TCR-transgenic animals is not formed properly and perhaps SLAM signaling is aborted. Finally, those TCRtransgenic animals that do have iNKT cells express a Vb gene that has been shown to associate with the invariant Va14 TCR chain in iNKT cells [1,2], and transgenic expression of such a compatible Vb chain has been shown to promote iNKT cell development [51]. P14 and DO11.10 mice express Vb8 (Vb8.1 and Vb8.2, respectively), while OT-I and OT-II mice express Vb5.…”
Section: Discussionmentioning
confidence: 99%
“…The competing model would predict that akin to mainstream T cells, Tcr gene segments rearrange randomly and the productive ones are subjected to positive and negative selection by CD1d1 and beget the NK T lineage -the stochastic model. Nucleotide sequence analyses of the V and J junctions within rearranged Va14Ja15 genes revealed that the canonical TCRa sequence of the CD1d1-reactive NK T cells is put together by random events that also include N nucleotide additions [133,172,173]. Moreover, the second allele also showed evidence of random rearrangement within the Tcr locus [133,172,173].…”
Section: Nk T Cell Ontogenymentioning
confidence: 99%
“…Nucleotide sequence analyses of the V and J junctions within rearranged Va14Ja15 genes revealed that the canonical TCRa sequence of the CD1d1-reactive NK T cells is put together by random events that also include N nucleotide additions [133,172,173]. Moreover, the second allele also showed evidence of random rearrangement within the Tcr locus [133,172,173]. More recently, genomic DNA sequence analysis of NK T cell-derived Vb8.2 transgenic thymocytes prior to selection (TCR low thymocytes) revealed random rearrangement of Va14 with Ja15 segments resulting in a high frequency of noncanonical Va14+ TCR a chain [173].…”
Section: Nk T Cell Ontogenymentioning
confidence: 99%
See 1 more Smart Citation